2013
DOI: 10.1299/kikaic.79.90
|View full text |Cite
|
Sign up to set email alerts
|

Design Theory and Vibration Characteristics of Contact Head Slider

Abstract: The design theory of the previously proposed contact head slider was extended by considering the intermolecular adhesion force and thermally protruding head slider. The microwaviness-excited vibration characteristics of the thermally protruding head slider were analyzed by using the JKR adhesive contact theory. An important fact revealed is that, owing to the adhesive force, the excited frequency of the contacting slider are changed from zero to a value higher than the original second mode resonance frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Using these methods, many previous studies reported on the relationship between the adhesion force and the surface roughness or surface energy of the sample [20][21][22][23][24][25][26][27][28][29][30][31]. There are also many other reports focusing on the effect of surface roughness on the adhesion and interaction of two contact bodies using different surface measurements and theoretical methods [32][33][34][35][36][37][38][39]. These reports suggest that the adhesion force between two contact solids is predictable; however, their application to many industrial machines is difficult because these theories and experimental results are based on static measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Using these methods, many previous studies reported on the relationship between the adhesion force and the surface roughness or surface energy of the sample [20][21][22][23][24][25][26][27][28][29][30][31]. There are also many other reports focusing on the effect of surface roughness on the adhesion and interaction of two contact bodies using different surface measurements and theoretical methods [32][33][34][35][36][37][38][39]. These reports suggest that the adhesion force between two contact solids is predictable; however, their application to many industrial machines is difficult because these theories and experimental results are based on static measurements.…”
Section: Introductionmentioning
confidence: 99%